The Effect of Ethical Leadership on Organizational Intentional Forgetting with the Mediating Role of Organizational Learning - Atefeh Keshtegar; Naser NastieZaie (مدیریت راهبردی دانش سازمانی, 2021)
The purpose of this study was to investigate of the effect ofethical leadership on organizational intentionalforgetting with the mediating role of organizational learning. This study was an applied and correlation research method based on structural equation modeling. 120 employees of Chabahar maritime and marine sciences university were studied by stratified random sampling method. To collect information, three questionnaires were used: ethical leadership, organizational intentionalforgetting and organizational learning. For data analysis the Pearson correlation coefficient and structural equation modeling were used by SPSS and Lisrel software. Based on results the relationships between ethical leadership, organizational intentional forgetting and organizational learning was positive and significant. The direct effect of ethical leadership on organizational intentionalforgetting (β=0.54, t=3.94), ethical leadership on organizational learning (β=0.8, t=8.24) and direct effect of organizational learning on organizational intentionalforgetting (β=0.44, t=3.17) was positive and significant. The indirect effect of ethical leadership on organizational intentionalforgetting was also significant with the mediator role of organizational learning (β=0.352, t=4.87). Therefore, it can be concluded that the managers of the organization can improve organizational learning and organizational forgetfulness by ethical leadership, involving employees in decision making, encouraging them to learn and exchange knowledge with each other, performing the role of ethical model and establishing an ethical and supportive environment in the organization.